Operative treatment in non-emergency sports injuries: a sports medicine clinic experience - Kara, Ö. S.; Torgutalp, S. S.; Turhan, E.; Dönmez, G.; Korkusuz, F. (The Physician and Sportsmedicine, 2023)
Purpose To elucidate referrals from sports medicine clinic (SMC) to orthopedics, consensus rates among physicians and surgeons on surgical need in these patients, and reasoning of the patients who refused to have surgery despite the recommendations by both groups in non-emergency sports injury patients.